Dewey’s Philosophy and Thoughts An analysis of the Compatible Applied on Islamic Education - Chamisah (JURNAL ILMIAH MAHASISWA, 2023)
The study's objective is to analyze the philosophy of John Dewey and its potential application in Islamic education. It aims to explore whether Dewey's ideas, which emphasize the role of experience in shaping human ideals and concepts, can harmonize with the Islamic philosophy of education, centered on the integration of senses, intellect, and religious faith to realize human values. The study will evaluate the compatibility of Dewey's emphasis on critical thinking and personal autonomy with Islamic teachings, which also recognize the significance of knowledge, science, and progress in improving human life. Wherever any ideas are found to be incompatible with Islamic education, the study will provide suggestions on how to improve or replace them to maintain the alignment with Islamic principles. Ultimately, the goal is to enrich Islamic education through a nuanced understanding of Dewey's philosophy and identify ways to bridge the gap between the two educational approaches, fostering a better human existence through continuous engagement and transformation of reality.